Topic : The impact of IT innovation in the fight against food insecurity in Sub-Saharan Africa (SSA) - Atekwana Mbekwa, Pierre-Alain; Syrovátková, Jana; Kubiš, Václav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
This thesis presents a review of 81 studies aimed at investigating the impact of IT innovations on agricultural productivity, food distribution systems, and access to vital information in sub-Saharan Africa. The research unveils substantial improvements in farming productivity and food distribution networks resulting from digital advisory services and information platforms. However, the study also uncovers several obstacles hindering the widespread adoption and effective utilization of these technologies, such as limited digital literacy, inadequate infrastructure, and restricted access to affordable internet services. To overcome these challenges and optimize the benefits of IT innovations in addressing food insecurity, the thesis proposes future research directions and targeted policy interventions. By addressing research gaps and implementing suitable policy frameworks, sub-Saharan Africa can effectively leverage IT innovations to achieve enduring food security and sustainable agricultural development.
Vedoucí práce: Jana Syrovátková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses